Development of a monoclonal antibody and a lateral-flow device for the rapid detection of a Mucorales-specific biomarker - Thornton, Christopher R.; Davies, Genna E.; Dougherty, Laura (Frontiers in Cellular and Infection Microbiology, 2023)
Mucoromycosis is a highly aggressive angio-invasive disease of humans caused by fungi in the zygomycete or-9 der, Mucorales. While Rhizopus arrhizus is the principal agent of mucoromycosis, other Mucorales fungi including 10 Apophysomyces, Cunninghamella, Lichtheimia, Mucor, Rhizomucor and Syncephalastrum are able to cause life-threat-11 ening rhino-orbital-cerebral, pulmonary, gastro-intestinal and necrotising cutaneous infections in humans. Diag-12 nosis of the disease currently relies on non-specific CT, lengthy and insensitive culture from invasive biopsy, and 13 time-consuming histopathology of tissue samples. At present, there are no rapid antigen tests that detect Mu-14 corales-specific biomarkers of infection, and which allow point-of-care diagnosis of mucoromycosis. Here, we 15 report the development of an IgG2b monoclonal antibody (mAb), TG11, which binds to extracellular polysaccha-16 ride (EPS) antigens of between 20 kDa and 250 kDa secreted during hyphal growth of Mucorales fungi. The mAb 17 is Mucorales-specific and does not cross-react with other yeasts and molds of clinical importance including As-18 pergillus, Candida, Cryptococcus, Fusarium, Lomentospora and Scedosporium species. Using the mAb, we have devel-19 oped a Competitive lateral-flow device that allows rapid (30 min) detection of the EPS biomarker in human serum 20 and bronchoalveolar lavage (BAL), with a limit of detection (LOD) in human serum of 100 ng/mL serum ( 224.7 21 pmol/L serum). The LFD therefore provides a potential novel opportunity for detection of mucoromycosis caused 22 by different Mucorales species.